On the Sofa. Forms of Being Together - Sanzeri , Elisa (E|C, 2024)
This essay offers a socio-semiotic analysis of the sofa’s transformations over time, aiming to identify the various forms of sociality it suggests and prefigures. The sofa is first examined in relation to domestic space and the transformations that take place within it. Given the key role of vision in shaping intersubjective spatiality, the arrangement of gazes generated by the sofa’s placement within the domestic setting is reconstructed. This analysis enables the identification of various formal structures of intersubjective spatiality and different configurations of the sofa. The next phase of the analysis considers the sofa as a space that contains bodies in relation to each other. It highlights how the sofa, depending on certain transformations in its shape, anticipates different ways of sitting and, consequently, different modes of relating to others. By analyzing the sensible qualities of the object, the various functions of the sofa are revealed, along with the different images of the body – both individual and relational – that it implies.